REMOVAL OF SODIUM, POTASSIUM AND CALCIUM METAL IONS FROM ALKALIZED SUGAR JUICE USING SUGAR BEET PULP: A FIXED-BED COLUMN BIOSORPTION STUDY - Perović, Lidija (Food and Feed Research, 2025)
This study investigates the possibility of applying continuous biosorption as an additional step in the sugar juice purification process to reduce the content of metal ions in alkalized juice. The response surface methodology (RSM) was used to examine the influence of the biosorption parameters: bed height of the biosorbent in the column, flow rate of the alkalized juice, and granulation of the biosorbent on molassigenic metal ions (K+, Na+ and Ca2+) removal efficiency. At a flow rate of 4.75 mL/min, a biosorbent bed height of 15 cm, and biosorbent granulation <1 cm, the achieved reduction of Na+ and Ca2+ ions in the alkalized juice was 74.19% and 62.78%, respectively. Slightly lower removal efficiency of K+ ions (50.69%) was achieved at a flow rate of 6.75 mL/min, a bed height of 15 cm, and biosorbent granulation >5 cm. Therefore, the biosorption process is highlighted as a desirable process in the thin juice purification stage. By repurposing the by-product of the sugar industry, the concept of circular economy and zero waste emission is achieved. An additional step in the juice purification process in the sugar industry results in higher juice purity, thereby enabling greater sugar extraction and yield.